The Hessdalen Lights Seen as the Aerial Counterpart of an Unsuspected Subsoil Phenomenon. Is the Earth Harboring a Multimouth Wormhole? - Pascoli, Gianni (Journal of Scientific Exploration, 2024)
To date, Hessdalen lights (HLs) are misunderstood; nevertheless, these phenomena are surprisingly ignored by most of the scientific community. However, a few researchers, such as Erling Strand and Massimo Teodorani, have paved the right path by showing that experimental methods of physics can be applied to study HLs. Additionally, we believe that matter cannot simply be brushed aside and that it deserves a serious examination. Recently, we proposed a possible origin of HLs (Pascoli, 2021). The basic idea—a micrometric wormhole manifestation—is promoted here, and we suggest that the Hessdalen-type lights, seen pretty much everywhere in the world, may eventually be interpreted as a symptom of an unsuspected phenomenon deep in the subsoil of the considered site. The idea of a geological origin for the Hessdalen lights has already been proposed (Teodorani, 2004, 2014); however, this interesting suggestion is being reconsidered from an entirely new perspective. The present paper has to be seen as a working hypothesis, in which the main interests are to foster thinking on underlying physics and to suggest a full series of experiments that can be performed on these very enigmatic Hessdalen lights. Regardless of the strength of a hypothesis, the experiment is the final arbiter in science.